The STEAM Approach: Implementation and Educational, Social and Economic Consequences - Miralimovna, Malika Yunusova (Research Parks Publishers, 2023)
Nowadays, STEAM-learning as a trend in world education accumulates the educational, developmental and educational potential of science, technology, engineering, creativity and mathematics. This training is based on an interdisciplinary and applied approach that integrates disciplines into a single training scheme and ensures the integration of the maximum number of skills. The context of STEAM education implies a mixed environment and shows how the scientific method can be applied in life. Currently, State programs in the field of using the STEAM educational system are being implemented in a number of highly developed countries. The article deals with the issues based on the content of the STEAM approach, the process of implementation and educational, social and economic consequences.